Pengaruh Capital Adequacy Ratio, Beban Operasional Pendapatan Operasional, Dan Loan To Deposit Ratio Terhadap Return On Assets Di Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2023 - Mariyo Napthali Ravelino Parapat; Immanuel Tambunan; Tiarmaida Togatorop; Maya Sabirina Panggabean; Dewi Nurmasari Pane (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to assess how CAR, BOPO, and LDR affect ROA. The quantitative method used in this study involves banking companies that have been registered and listed on the Indonesia Stock Exchange from 2021 to 2023. A total of 39 banking companies were sampled, and the data can be accessed on the official website of the Indonesia Stock Exchange. The data were analyzed using SPSS 30 and a multiple linear regression approach. The analysis shows that there is an effect of the CAR variable on ROA, while the BOPO and LDR variables do not have an individual effect on ROA. However, when viewed as a whole, all three variables show a significant impact on ROA.